Effectiveness of Facebook-Delivered Lifestyle Counselling and Physical Activity Self-Monitoring on Physical Activity and Body Mass Index in Overweight and Obese Adolescents: A Randomized Controlled Trial - Heidi Ruotsalainen; Helvi Kyngäs; Tuija Tammelin; Hanna Heikkinen; Maria Kääriäinen (Nursing Research and Practice)
Background. The aim was to evaluate the effects of a 12-week, Facebook-delivered lifestyle counselling intervention, with or without physical activity self-monitoring, on physical activity and body mass index (BMI) in overweight and obese 13–16-year-old adolescents. Methods. Three-arm randomized controlled trial. Participants (n=46) were randomly assigned to intervention and control groups: one group received Facebook-delivered lifestyle counselling and monitoring of their physical activity (Fb + Act, n=15), whereas a second experimental group received the same Facebook-delivered lifestyle counselling without self-monitoring (Fb, n=16) and a third group served as the control group (n=15). Objective and self-reported physical activity assessment were used. Nonparametric statistical tests were used. Results. There were no significant intervention effects in terms of changes in physical activity levels or BMI from baseline to the 12-week postintervention measurements between the intervention and control groups. The Fb + Act group had lower sedentary time on weekdays compared to the control group during postintervention measurements (p=0.021), but there was no interaction between time and group. Conclusions. Interventions were not effective at increasing physical activity in overweight and obese adolescents. Before implementing such interventions, more evaluations on their effectiveness are needed. This trial is registered with ClinicalTrials.gov identifier NCT02295761 (2014-11-17).